2013
DOI: 10.1016/j.amjcard.2013.05.016
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Echocardiographic Method to Estimate Pulmonary Vascular Resistance

Abstract: Pulmonary hypertension is comprised of heterogeneous diagnoses with distinct hemodynamic pathophysiology. Identifying elevated pulmonary vascular resistance (PVR) is critical for appropriate treatment. We reviewed data for patients seen at referral PH clinics who underwent echocardiography and right heart catheterization within 1 year. We derived equations to estimate PVR based on the ratio of estimated pulmonary artery (PA) systolic pressure (PASPDoppler) to RVOT VTI. We validated these equations in a separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 27 publications
2
58
1
1
Order By: Relevance
“…Interestingly, the Opotowsky method had a superior receiver-operating characteristic curve for discrimination of PVR >3 Wood units compared with the Abbas method. 41 Finally, Choi et al 42 showed that Definity dye transit time from peak opacification of right ventricle to first appearance in the left ventricle could be used to estimate PVR and cardiac output. In that study, the transit time for the contrast to travel from the right ventricle to the left ventricle was directly proportional to PVR and inversely proportional to cardiac output.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the Opotowsky method had a superior receiver-operating characteristic curve for discrimination of PVR >3 Wood units compared with the Abbas method. 41 Finally, Choi et al 42 showed that Definity dye transit time from peak opacification of right ventricle to first appearance in the left ventricle could be used to estimate PVR and cardiac output. In that study, the transit time for the contrast to travel from the right ventricle to the left ventricle was directly proportional to PVR and inversely proportional to cardiac output.…”
Section: Discussionmentioning
confidence: 99%
“…Whenever TR or PR was detected the Doppler beam was aligned as parallel as possible with the regurgitant flow in order to determine peak velocities and calculate peak pressure gradient (PG) using the modified Bernoulli equation (P ¼ 4 Â V max 2 ) and estimate peak systolic and mean PAP, respectively. Estimated right atrial pressures were not added to the calculated TR gradient, but a fixed right atrial pressure was added for calculating PVR (see in the following) [27]. Pulmonary hypertension was defined as a peak TR >2.8 m/s (estimated systolic PAP >30 mmHg) and/or peak PR >2.2 m/s (estimated d Vivid 7, GE Medical Systems, Munich, Germany.…”
Section: Animals Materials and Methodsmentioning
confidence: 99%
“…In cases in which no regurgitant jet was present hemodynamically significant PH was defined by the presence of RV hypertrophy/ dilatation, septal flattening, dilated main pulmonary artery in the absence of pulmonic stenosis and decreased left ventricle (LV) chamber size [28]. Pulmonary vascular resistance was calculated from estimated systolic pulmonary arterial pressure (sPAP) using a constant right atrial pressure of 8 mmHg (sPAP ¼ 8 þ 4 Â TR2) and RV outflow tract time-velocity integral using the following formula: PVR ¼ sPAP/RV outflow tract timevelocity integral þ 3 if mid-systolic notch (type III) [27]. Pulsed wave tissue Doppler imaging was performed to evaluate RV longitudinal myocardial velocities at the tricuspid lateral annulus using a standard left apical four-chamber view.…”
Section: Animals Materials and Methodsmentioning
confidence: 99%
“…[13][14][15] Left atrial size, tissue Doppler, and mitral inflow velocity patterns may identify elevated left atrial pressure (case, Figure 3B), although this does not preclude coexisting increases in PVR. …”
Section: Diagnosis: Echocardiographymentioning
confidence: 99%